The Swedish Literature Bank: Free Works - Språkbanken Text (University of Gothenburg, 2024)
The corpus contains all free e-texts and searchable facsimiles from the Swedish
Literature Bank, a freely available collection of Swedish literary works, ranging from medieval to contemporary.

Korpusen består av alla fria e-texter och sökbara faksimiler från Litteraturbanken,
en fritt tillgänglig samling av svenska skönlitterära texter från medeltiden till nutiden.
Litteraturbanken: fria verk
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik